2021
DOI: 10.1108/caer-09-2020-0221
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grassland transfer on herders' livestock production and grazing intensity in Inner Mongolia and Gansu, China

Abstract: Purpose The purpose of this study is to understand the impact mechanism of grassland transfer on herders' production behaviour in pastoral areas. The impact of grassland transfer on herders' livestock production and grazing intensity is quantified.Design/methodology/approach Using the survey data collected for 356 herder households from Inner Mongolia and Gansu, China, quantile regression is employed to assess the heterogeneous effects of grassland transfer on livestock production and grazing intensity. To cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…As for the response process of herder households, there are very few related studies. Some scholars found that when many herder households in pilot areas received compensation and did not reduce livestock as required, they often attributed the reason to the lack of a supervision system [64,65]. We agree that strong supervision will certainly help herder households to reduce livestock and improve compensation efficiency.…”
Section: Summary and Analysis Of Theoretical Researchmentioning
confidence: 85%
See 2 more Smart Citations
“…As for the response process of herder households, there are very few related studies. Some scholars found that when many herder households in pilot areas received compensation and did not reduce livestock as required, they often attributed the reason to the lack of a supervision system [64,65]. We agree that strong supervision will certainly help herder households to reduce livestock and improve compensation efficiency.…”
Section: Summary and Analysis Of Theoretical Researchmentioning
confidence: 85%
“…However, such compensation's effect is always inefficient, because it is difficult for herder households to spontaneously change the current production status without the support of training, supervision, equipment, etc. [64,65]. Industrial compensation is currently in the exploratory stage, and its purpose is to help herder households get rid of their dependence on traditional livestock husbandry.…”
Section: Research On Compensation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that plant communities are often found to have a mosaic distribution at different spatial scales ( 58 ). Even at a small local scale, the composition and biomass of palatable pasture may differ due to the effects of soil water content ( 54 ), grazing intensity ( 57 , 59 ) and animal excrement ( 60 ). In fact, temporal variability in livestock behaviors has been reported in some previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…(1)Herders acquire relevant grassland ecological knowledge through mobile phone media multi-communication channels (WeChat, public numbers, TikTok, etc. ), which broadens the individual's ecological cognitive horizons from the acquaintance community to the vast network society, constantly refreshes herders' understanding and desire for grassland ecosystems, improves the perception of the risks faced due to ecological damage, strengthens the ability to take action for ecological protection, and reduces the perceptual chances and inaccuracies, which are a critical subconscious dominant factor in increasing predictable behavior for livelihood transformation; (2) The increasing improvement of informatization facilities in pastoral areas has simplified and broadened the difficulty and channels of obtaining information, weakened the cost of getting ecological knowledge, improved the accuracy of the information received, reversed the asymmetry and incompleteness of information dissemination among herder groups, and to a certain extent enhanced the herders' awareness of ecological protection. Consequently, the enhancement of herders' ecological cognition pertaining to harmonious practices contributes to their perception of the extent of grassland degradation, comprehension of the grassland ecological subsidy policy, and confidence in grassland ecological protection.…”
Section: The Role Of Grassland Ecological Cognition In the Intensity ...mentioning
confidence: 99%